2021
DOI: 10.1186/s13765-021-00654-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid metabolism enzyme activities and gene expression in postharvest melons inoculated with Alternaria alternata

Abstract: This study explored the mechanism of melon resistance to Alternaria alternata (A. alternata) infection in Jiashi and 86-1 melons. Melons were inoculated with A.alternata and the change in lesion diameter was measured. The changes in cinnamic acid-4-hydroxylase (C4H), phenylalanine ammonia lyase (PAL), and 4-coumaric acid coenzyme A ligase (4CL) activity and gene expression were studied in the pericarp tissues of Jiashi and 86-1 melons. The lesion diameter was smaller in Jiashi melon than in 86-1 melon, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Degradation of PAL activity in ozone-treated chili fruits started to occur only at 20 days (Sachadyn-Król et al, 2016). Bai et al (2021) reported that inoculating Streptomyces spp. into cantaloupes enhanced enzyme activity in cantaloupes promoted lignin synthesis and improved disease resistance in cantaloupes.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of PAL activity in ozone-treated chili fruits started to occur only at 20 days (Sachadyn-Król et al, 2016). Bai et al (2021) reported that inoculating Streptomyces spp. into cantaloupes enhanced enzyme activity in cantaloupes promoted lignin synthesis and improved disease resistance in cantaloupes.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 4CL and C4H are key enzymes in phenylpropanoid metabolic pathway in flavonoid biosynthesis. Some studies have shown that when the expression levels of 4CL and C4H are high in pear and other plants, the content of flavonoid also increases (Bai et al, 2021;Shahivand et al, 2021). But in Lonicera macranthoides, 4CL and C4H negatively regulate the production of flavonoids downstream (Pan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PAL and cinnamic acid coenzyme A ligase (4CL) play a key role in lignin biosynthesis. PAL is the main rate-limiting enzyme that converts L-phenylalanine into trans-cinnamic acid by eliminating ammonia, with its isomers playing a unique but redundant role in plant growth and stress response ( Bai et al., 2021 ). Moreover, 4CL acts as the main branch point enzyme controlling the biosynthesis of downstream molecules, particularly flavonoids and lignans.…”
Section: Discussionmentioning
confidence: 99%